ENHANCING LOCAL GOVERNANCE THROUGH INNOVATIVE STATE MONITORING AND AUDIT PRACTICES - X.X.Xudoyqulov,; Pazlitdinov Abbosbek Akram o’g’li, (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstract: This article examines the enhancement of local governance through the adoption of innovative state monitoring and auditing practices. By evaluating various international frameworks for public sector oversight, the study identifies effective strategies that promote transparency, accountability, and efficiency in local administration. It highlights case examples from diverse countries, demonstrating how tailored approaches can address prevalent challenges in local government oversight. Ultimately, the research aims to provide actionable recommendations for local policymakers seeking to improve governance systems by leveraging global best practices.